K3 Socialization in a New Normal Situation for Building Workers in Stikes St. Elisabeth - Suhadi Suhadi; Maria Theresia Priyastuti; Emirensiana Anu Nono; Maria Karolina Selano; Hubertus Agung Pambudi (Global Health Science Group, 2020)
The COVID-19 pandemic that has hit all countries shows an important function of organizing K3 for each field of work. In addition to ensuring the workplace is safe to use, K3 is very important to ensure health and limit the spread of viruses that are easily transmitted. That way, the application of K3 in the work area is key in protecting the health of workers and their families. Community service activities aim to conduct socialization related to occupational safety and health (K3) to construction workers CV DRB (Domen Rancang Bangun) in the STIKes St. Elisabeth. This is important in an effort to prevent the spread of the Corona virus at work sites. Various efforts need to be made to prevent the spread of the Covid - 19 virus in the work environment in the application of the new normal, including the creation and dissemination of health protocol SOP in areas / building locations in the STIKes environment. The method used in this activity is by planning, implementing, observing and evaluating the implementation of K3 socialization in a new normal situation for construction workers. The result of this service activity is the creation, installation and socialization of educational media in the form of posters and banners as a means of media for health education for the New Normal Covid-19 in the STIKes St. Elisabeth, the increasing form of caring for others in the New Normal Covid -19 life pattern in the STIKes St. Elisabeth by providing guaranteed protection facilities for workers from the corona virus by providing masks and hand washing facilities.